Analisis Keselarasan Kebijakan Dalam Pembentukan Regulasi Pengembangan Kawasan Metropolitan Rebana Provinsi Jawa Barat - Elsa Gustini Vinsensia S; Wiranata Nababan (Journal of Global Legal Review, 2026)
This study aims to analyze policy alignment in the development regulations of the Rebana Metropolitan Area in West Java Province, identify factors causing regulatory disharmony, and formulate a regulatory harmonization model that can support the effectiveness of regional development. The study uses a normative legal method with a statute approach and a conceptual approach. Data were obtained through a literature review of relevant laws and regulations, development planning documents, books, and scientific journals. The results indicate that normatively, the development regulations of the Rebana Metropolitan Area have a fairly good level of policy alignment, particularly between Presidential Regulation Number 87 of 2021, the West Java Governor's Regulation, and various spatial planning and regional development documents. However, there is still potential for regulatory disharmony caused by overlapping authorities, unsynchronized planning documents, weak coordination between institutions, and the dynamics of development policies. Therefore, a regulatory harmonization model is needed through strengthening vertical and horizontal policy synchronization, optimizing the role of the Rebana Area Management Agency, and continuous regulatory evaluation to realize integrated, effective, and sustainable regional development.